Metal Concentrations in Two Bioindicator Fish Species, Merlangius merlangus, Mullus Barbatus, Captured from the West Black Sea Coasts (Bartin) of Turkey - Fındık, Ö; Çiçek, E (Springer Science and Business Media LLC, 2011)
The Black Sea is very vulnerable to originating from land based human activities and its health is equally dependent on the coastal and non-coastal states of its basin. Total concentrations of cadmium, copper, zinc, lead, nickel, aluminum, iron, manganese, boron and chromium concentrations were determined in Merlangius merlangus (whiting) and Mullus barbatus found in Amasra in the West Coast of the Black Sea (Turkey). The metal contents that were measured in head and muscle was expressed in μg g(-1) wet weight. On average, while the highest Fe (344.25 μg g(-1)), Mn (10.35 μg g(-1)), Cr (0.96 μg g(-1)) and Al (76.77 μg g(-1)) concentrations were measured in the heads of M. merlangus and the highest Zn (77.99 μg g(-1)), Cu(8.53 μg g(-1)), B (44.83 μg g(-1)), Ni (1.96 μg g(-1)), Cd (0.40 μg g(-1)) and Pb (6.80 μg g(-1)) concentrations were detected in the muscles of M. merlangus. There were significant differences between metal levels of muscles in these two species. In terms of permissible levels reported by WHO FAO and TSE, there is not any risk for human consumption for both M. merlangus and M. barbatus, for Pb.
Keywords: Turkey; Risk Assessment; Perciformes; Gadiformes; Black Sea; Metals; Water Pollution, Chemical; Animals; Water Pollutants, Chemical; Environmental Monitoring; 13. Climate action; 14. Life underwater